Analisis Implementasi Penyusunan Laporan Keuangan pada Persediaan di Koperasi Druju Kabupaten Malang - Ahmad 'Azam 'Ulwan; Yuliati Yuliati (Jurnal Ekonomi Akuntansi dan Manajemen, 2023)
Cooperatives are a type of enterprise that can increase a nation's economy and lessen poverty. Equity is where the cooperative gets its money, therefore if stock is running well, the financial reports will be accurate. However, this is frequently overlooked, leading to issues with accounting results in the areas of shopping, savings, and lending. This study employs a qualitative approach and then a descriptive method using field phenomena. The data analysis process involved gathering data through field observations, interviewing Druju Cooperative informants, analyzing inventory accounting, describing the analysis, documenting field circumstances, and drawing conclusions. The study's findings show that the Financial Accounting Standards for Entities Without Public Accountability financial reports are insufficient because of the employee's lack of expertise and the accounts included in the financial statements (SAK ETAP). Keywords: Cooperatives, Financial Statements, Inventory